8-Substituted 1, 3-dimethyltetrahydropyrazino[2, 1-f]purinediones: Water-soluble adenosine receptor antagonists and monoamine oxidase B inhibitors. Issue 21 (1st November 2016) - Brunschweiger, Andreas; Koch, Pierre; Schlenk, Miriam; Rafehi, Muhammad; Radjainia, Hamid; Küppers, Petra; Hinz, Sonja; Pineda, Felipe; Wiese, Michael; Hockemeyer, Jörg; Heer, Jag; Denonne, Frédéric; et al.
Graphical abstract: Highlights: A series of 61 diversely substituted pyrazinopurinediones was synthesized. Aromatic residues were connected to the core heterocyclic structure by different linkers. Their adenosine receptor affinities and monoamine oxidase inhibitory potencies were investigated. Several compounds showed higher water-solubility than the isomeric pyrimidopurinediones. Multi-target drugs were designed and optimized for neurodegenerative diseases. Abstract: Multitarget approaches, i.e., addressing two or more targets simultaneously with a therapeutic agent, are hypothesized to offer additive therapeutic benefit for the treatment of neurodegenerative diseases. Validated targets for the treatment of Parkinson's disease are, among others, the A2A adenosine receptor (AR) and the enzyme monoamine oxidase B (MAO-B). Additional blockade of brain A1 ARs may also be beneficial. We recently described 8-benzyl-substituted tetrahydropyrazino[2, 1- f ]purinediones as a new lead structure for the development of such multi-target drugs. We have now designed a new series of tetrahydropyrazino[2, 1- f ]purinediones to extensively explore their structure–activity-relationships. Several compounds blocked human and rat A1 and A2A ARs at similar concentrations representing dual A1 /A2A antagonists with high selectivity versus the other AR subtypes. Among the best dual A1 /A2A AR antagonists were 8-(3-(4-chlorophenyl)propyl)-1, 3-dimethyl-6, 7, 8, 9-tetrahydropyrazino[2, 1- f ]purine-2, 4(1 H, 3 H )-dione (41, K i human A1 : 65.5 nM, A2A : 230 nM; K i rat A1 : 352 nM, A2A : 316 nM) and 1, 3-dimethyl-8-((2-(thiophen-2-yl)thiazol-4-yl)methyl)-6, 7, 8, 9-tetrahydropyrazino[2, 1- f ]purine-2, 4(1 H, 3 H )-dione (57, K i human A1 : 642 nM, A2A : 203 nM; K i rat A1 : 166 nM, A2A : 121 nM). Compound57 was found to be well water-soluble (0.7 mg/mL) at a physiological pH value of 7.4. One of the new compounds showed triple-target inhibition: ( R )-1, 3-dimethyl-8-(2, 1, 3, 4-tetrahydronaphthalen-1-yl)-6, 7, 8, 9-tetrahydropyrazino[2, 1- f ]purine-2, 4(1 H, 3 H )-dione (49 ) was about equipotent at A1 and A2A ARs and at MAO-B ( K i human A1 : 393 nM, human A2A : 595 nM, IC50 human MAO-B: 210 nM) thus allowing future in vivo explorations of the intended multi-target approach.